Perceptions and experiences of interventions to prevent postnatal depression: a systematic review and qualitative evidence synthesis - Scope, Alison; Booth, Andrew; Morrell, C. Jane; Sutcliffe, Paul; Cantrell, Anna (Elsevier, 2017)
Background